Mathematical Study on a Non-Darcian Flow of a Nanofluid - Sathyapriya, B.; Subha, M.; Sivasankari, S.; Ananthaswamy, V. (Journal of Applied Nonlinear Dynamics, 2026)
The flow of two dimensional Buogiorno nanofluid across an extending sheet having magnetic effect with a non-Darcy porous medium is explored analytically. By applying the transformation of similarity, the associated dimensional equations are simplified into dimensionless equations. With the aid of Ananthaswamy-Sivasankari approach and Modified Homotopy Analysis Technique, the expressions regarding the corresponding non-dimensional temperature, velocity, and concentration equations are attained. When the outcomes are compared to the numerical solution, a very excellent fit is found. Numerous controlling parameters including magnetic, porosity and thermophoresis are graphically depicted to reveal how they affect the flow. Furthermore, the physical parameters, especially~the reduced number of Sherwood, and the reduced number of Nusselt are visually displayed.